Epidemiological Surveillance of Tuberculosis: from Molecular Methods to Genomic Studies - O. B. Ogarkov; E. D. Savilov; S. N. Zhdanova (Эпидемиология и вакцинопрофилактика)
Relevance. The globalization of the epidemic process requires improved surveillance of infectious diseases, in particular tuberculosis.Methods of molecular and genomic analysis are the most informative approaches that can radically change the management of this disease.Aims. To substantiate the necessary and sufficient volume of molecular studies for the exhaustive detection of most epidemic genotypes of Mycobacterium tuberculosis in Russia and the countries of the former USSR.Conclusions. Genetic lines L2 (Beijing) and L4 (Euro-American) cover more than 95% of all epidemic genotypes of M. tuberculosis in Russia and the countries of the former USSR. The development of rapid tests compatible with global data on genomic polymorphism will make it possible to conduct an epidemiological analysis of tuberculosis outbreaks within the country and to differ from cases of transbordern transmission of new genotypes outside.